Molecular Energy Concept of Substances Unpacking - Haydarov G. G., Haydarov A. G. (Interactive science, 2021)
this article brings together previously published evidence of the unified nature of physical processes and phenomena in terms of changes in the energy of a substance molecule. The unified physical nature of all these physical phenomena has been proven, as a single multistage process of energetic unpacking of molecules of a substance, which is logical to call the molecular-energy concept of unpacking a substance. The considered processes include the following processes. Surface rupture, characterized by the surface tension coefficient. The melting process of a substance characterized by its melting point. A boiling process characterized by the boiling point. Evaporation (and condensation) process characterized by internal energy and enthalpy as well as critical point. The conclusions of the theory are confirmed by well-known empirical dependences and by reference books of the physical properties of simple substances: internal energy, enthalpy, surface tension, melting point, boiling point and critical point.
Keywords: энергия; физика; плавление; температура; зависимость; теория; взаимосвязь; справочные; данные; связь; вещество; energy; data; формула; кипение; распаковка; physics; substance; theory; formula; temperature; unpacking; correlation; melting; boiling; reference; interrelation; поверхностное; натяжение; молекула; молекулярная теория; molecule; molecular theory; surface tension; connection